Photosynthetic performance of Antarctic lichen Dermatocarpon polyphyllizum when affected by desiccation and low temperatures - Bednaříková, Michaela; Váczi, Peter; Lazár, Dušan; Barták, Miloš (Photosynthesis research, 2020)
Lichens are symbiotic organisms that are well adapted to desiccation/rehydration cycles. Over the last decades, the physiological background of their photosynthetic response-specifically activation of the protective mechanism during desiccation-has been studied at the level of photosystem II of the lichen photobiont by means of several biophysical methods. In our study, the effects of desiccation and low temperatures on chlorophyll fluorescence and spectral reflectance parameters were investigated in Antarctic chlorolichen Dermatocarpon polyphyllizum. Lichen thalli were collected from James Ross Island, Antarctica, and following transfer to a laboratory, samples were fully hydrated and exposed to desiccation at temperatures of 18, 10, and 4 °C. During the desiccation process, the relative water content (RWC) was measured gravimetrically and photosynthetic parameters related to the fast transient of chlorophyll fluorescence (OJIP) were measured repeatedly. Similarly, the change in spectral reflectance parameters (e.g., NDVI, PRI, G, NPCI) was monitored during thallus dehydration. The dehydration-response curves showed a decrease in a majority of the OJIP-derived parameters (e.g., maximum quantum yield of photosystem II photochemistry: FV/FM, and performance index: PI in D. polyphyllizum, which were more apparent at RWCs below 20%. The activation of protective mechanisms in severely dehydrated thalli was documented by increased thermal dissipation (DI0/RC) and its quantum yield (Phi_D0). Low temperature accelerated these processes. An analysis of the OJIP shape reveals the presence of K-bands (300 μs), and L-bands (80 μs), which can be attributed to dehydration-induced stress. Spectral reflectance indices decreased in a majority of cases with an RWC decrease and were positively related to the OJIP-derived parameters: FV/FM (capacity of photosynthetic processes in PSII), Phi_E0 (effectiveness of electron transport), and PI_tot (total performance index), which was more apparent in NDVI. A negative relation was found for NPCI. These indices could be used in follow-up ecophysiological photosynthetic studies of lichens that are undergoing rehydration/dehydration cycles.
Keywords: fotosyntéza; Stress; Photosynthesis; voda; Adaptation, Physiological; Fast chlorophyll fluorescence curve; Antarktida; lišejníky; dehydratace; fyziologická adaptace; Antarctic Regions; Dehydration; Cold Temperature; Desiccation; Photosystem II Protein Complex; Upper cortex; vysoušení; Ascomycota; Lichens; OJIP; nízká teplota; Water; fotosystém II (proteinový komplex); Spectral reflectance